A Case of Recurrent Painful Ophthalmoplegic Neuropathy - Yan, Yaping; Zhang, Bo; Lou, Zhuocong; Liu, Kaiming; Lou, Ming; Ding, Meiping; Xu, Yongfeng (Frontiers in Neurology, 2020)
Ophthalmoplegic migraine (OM) is characterized by recurrent episodes of headache with unilateral ophthalmoplegia due to paresis of cranial nerve III, IV, or VI. The recent revision to the International Headache Classification has reclassified it as recurrent painful ophthalmoplegic neuropathy (RPON). However, it is of note that the presentation of oculomotor nerve tumours may mimic RPON. Here, we report the case of a patient presenting with recurrent migraine and oculomotor palsy with several specific magnetic resonance imaging (MRI) findings. The patient was initially diagnosed with migraine 15 years ago, but since 10 years ago, his symptoms had evolved to include repeated oculomotor paralyses. Before this attack, the patient did eventually recovered completely each time after the initial episode. MRI performed during this attack revealed a nodular enhancing lesion described as schwannoma of the left oculomotor nerve, while on diffusion weighted imaging (DWI), the nerve was isointense to the midbrain. The nodular enhancement became weaker, and the nerve’s signal on DWI disappeared 3 months later as the patient’s symptoms resolved mostly. This is the first case of RPON demonstrating an obvious change in signal of the affected nerve on DWI during the attack and remission.